Understanding physics for advanced levell - Breithaupt, Jim (Cheltenham : Nelson Thornes, 2000)
The fourth edition of this best-selling Student Book covers popular options including particle physics, relativity and quantum physics, materials and astronomy. Written with great clarity and extensively illustrated, hundreds of experiments are discussed and worked examples are presented throughout.
Keywords: Physique